2017
DOI: 10.1016/j.bjid.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of human parvovirus B19 during two outbreaks of erythema infectiosum in Brazil

Abstract: This study was conducted to provide information on the genetic diversity of human parvovirus B19 (B19V) circulating in the municipality of Niterói, Rio de Janeiro, Southeast Brazil during 1996-2006, a period with two distinct outbreaks of B19V infection: 1999-2000 and 2004-2005. A total of 27 sera from patients with erythema infectiosum and five sera from HIV-infected patients that tested positive for B19V DNA during the study period were analyzed. To genotype B19V strains, a semi-nested PCR for partial amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In respect of B19V circulating virus strains, our study corroborates a recent work that stated that genotype 1 is the most worldwide spread type, being followed by the rare genotype 3b. 63 , 64 In Brazil, other previous studies had demonstrated the existence of genotypes 1, 2, and 3, 42 , 49 whereas others detected only 1 and 3 genotypes 48 , 65 or solely genotype 1. 50 , 66 …”
Section: Discussionmentioning
confidence: 80%
“…In respect of B19V circulating virus strains, our study corroborates a recent work that stated that genotype 1 is the most worldwide spread type, being followed by the rare genotype 3b. 63 , 64 In Brazil, other previous studies had demonstrated the existence of genotypes 1, 2, and 3, 42 , 49 whereas others detected only 1 and 3 genotypes 48 , 65 or solely genotype 1. 50 , 66 …”
Section: Discussionmentioning
confidence: 80%
“…Genotype 1 is the most prevalent in the world. In Brazil, the three genotypes have already been detected, but there is also a predominance of Genotype 1 ( Freitas et al, 2008 ; Garcia et al, 2023 ). The first complete genome of B19V genotype 1 a was from a serum sample suspected of dengue infection, from a fatal case of a 12-year-old boy in Rio de Janeiro, Brazil ( Conteville et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parvovirus B19 infection may be asymptomatic or may present with prodromal symptoms only. In some cases, the prodrome is followed by a subsequent phase with more specific symptoms, while in other cases, as in immunosuppressed or high-risk individuals, the infection may progress to a chronic form associated with long-term complications and sequelae [19,20]. However, parvovirus infection can be asymptomatic in more than 50% of non-pregnant women and almost 30-50% of pregnant women, respectively [21].…”
Section: Maternal Infection-clinical Presentationmentioning
confidence: 99%
“…EI is the most classic sign of the disease and is more common in children. It is characterized by a "slapped face" appearance with a maculopapular rash on the face and/or trunk and extremities, which may present as a reticular rash [19,20].…”
Section: Maternal Infection-clinical Presentationmentioning
confidence: 99%